(untitled) (Journal of Fiber Bioengineering and Informatics, 2019)
The experiment recruited 18 young healthy males as the subjects. Four postures with a limited range of movement during outdoor activity were captured by the mean of a 3D scanning system. The grids of rows and columns were made on the skin surface before scanning. The grids’ distance in terms of skin stretch was measured between the static posture and the four experimental postures. A paired sample T-test was conducted to test that the variation in skin length change for each part of the body. Among them, there were more significant changes in the horizontal direction for the small shoulder width, back width, bust, hip, thigh circumference, knee circumference, big arm circumference and elbow circumference. In the vertical direction, except for the inner lines of the legs, all measured sizes changed significantly. Through further analysis, it was found that the back length and the back width were relatively active factors that affected the entire upper limb movement. Finally, according to the changes in the measured sizes, it is necessary to explore protective clothing in terms of ease.